Labor competencies of the manager of human talent, according to current requirements of the organizations (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
The objective of this research was to analyze the labor competencies of the human talent manager in their performance within the current organizations located in the industrial zone II, Barquisimeto State Lara. The research was developed under a non-experimental modality of empirical type with quantitative methodology, under a field design with a descriptive level. The finite universe, was made up of professionals graduated from the XII promotion in 2013, represented by fifty (50) subjects. The intentional sample consisted of five (5) managers from the area of human talent, from five (5) selected companies, to which two (2) questionnaires were applied; the "A" questionnaire consisting of eight (8) closed questions with the option of multiple answers, to identify competences. The reliability under the Cronbach's Alpha method yielded 0.91, and was validated by expert judgment, and the "B" questionnaire, based on the performance management model of Martha Alles to contrast the profile of the career with the competencies that demand the organizations. The results of the study showed that the competences that the professionals possess fulfill in a highly satisfactory manner aspects to meet the current requirements of the organizations, however it was recommended to include in the profile of the graduate theoretical and practical aspects that provide the professional with the tools so that once active in the working world, it can develop in a more efficient way, skills related to the planning of preventive actions to manage changes in the short term.
Keywords: labor competencies; human talent management; current organization